Integrating 21st-Century Skills into Vocational Education Curricula: A Systematic Literature Review and Bibliometric Analysis - Dede Syukrillah Rifai; Sunar Wahid; Bambang Sumadyo (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2026)
Background of the study: Rapid digitalization, automation, and labor-market transformation require vocational education to integrate 21st-century skills into curricula, pedagogy, assessment, and industry-based learning. Purpose: This study maps research trends and synthesizes evidence on the integration of 21st-century skills in vocational education curricula, focusing on digital literacy, employability, Teaching Factory, and pedagogical innovation. Method: A systematic literature review supported by bibliometric analysis was conducted using Scopus-indexed publications from 2018 to 2025. Following a PRISMA-based screening process, 22 records were used for bibliometric mapping, while 9 core articles directly related to curriculum-level integration were included in thematic synthesis. Findings: The findings indicate that research is concentrated on digital literacy, project-based learning, technology-enhanced learning, work readiness, and Teaching Factory models. However, the integration of 21st-century skills remains fragmented across curriculum design, assessment practices, teacher professional development, and industry collaboration. Conclusion: Vocational education has increasingly adopted digital and industry-oriented pedagogies, but more coherent curriculum frameworks, valid assessment models, and cross-national studies are needed to support sustainable 21st-century skills integration.